272 Aggressive Diffuse Leptomeningeal Glioneuronal Tumor: A Challenging Diagnosis. (11th January 2018) - Villatoro, Tatiana; Curtis, Mark
Abstract: Introduction: Diffuse leptomeningeal glioneuronal tumor (DLGT) is a rare neoplasm characterized by a leptomeningeal infiltration by monomorphic small tumor cells. DLGT often presents with symptoms of increased intracranial pressure and meningeal involvement. Radiologic studies show diffuse leptomeningeal enhancement. Because the symptoms and radiologic appearance are not typical for a tumor, this entity is often not considered at presentation. Diagnosis is most commonly obtained postmortem. Methods: We present a surgical case of DLGT diagnosed antemortem in a young woman to emphasize the importance of considering this entity in the clinical and pathologic differential. Results: A 45-year-old woman presented with a 2-month history of nausea, vomiting, headache, dizziness, and blurry vision. Examination revealed bilateral papilledema and right cranial nerve six palsy. Intracranial pressure was markedly elevated (49 cm H2 O) and the CSF protein level was increased (950 mg/dL). Multiple radiologic studies of the head were unremarkable. A meningoencephalitis panel was negative. The patient was initially treated for presumed idiopathic intracranial hypertension. Magnetic resonance imaging (MRI) of the thoracic spine revealed an enhancement of the meninges throughout the neuraxis with an intramedullary mass causing near complete obstruction of the spinal canal. Radiologic studies of the abdomen and pelvis were unremarkable. Differential diagnoses included atypical infection and neoplastic processes. An initial lumbar biopsy was not diagnostic. A second diagnostic biopsy revealed a highly proliferative, astrocytic appearing neoplasm. The tumor diffusely infiltrated the leptomeninges, peripheral nerves, and focally penetrated the spinal parenchyma. The tumor cells were strongly GFAP positive, and negative for IDH-1, EMA, and p53. A high proliferation index was also noted (26%). Conclusions: Diffuse leptomeningeal glioneuronal tumor can clinically mimic idiopathic intracranial hypertension or atypical CNS infection. Recent reports suggest chemotherapy and radiotherapy are effective; hence, a clinical suspicion of this disease should be followed by an aggressive diagnostic strategy.